Senolytic Peptide FOXO4-DRI Selectively Removes Senescent Cells From in vitro Expanded Human Chondrocytes - Huang, Yuzhao; He, Yuchen; Makarcyzk, Meagan J.; Lin, Hang (Frontiers in Bioengineering and Biotechnology, 2021)
Autologous chondrocyte implantation (ACI) is a procedure used to treat articular cartilage injuries and prevent the onset of post-traumatic osteoarthritis. In vitro expansion of chondrocytes, a necessary step in ACI, results in the generation of senescent cells that adversely affect the quality and quantity of newly formed cartilage. Recently, a senolytic peptide, fork head box O transcription factor 4-D-Retro-Inverso (FOXO4-DRI), was reported to selectively kill the senescent fibroblasts. In this study, we hypothesized that FOXO4-DRI treatment could remove the senescent cells in the expanded chondrocytes, thus enhancing their potential in generating high-quality cartilage. To simulate the in vitro expansion for ACI, chondrocytes isolated from healthy donors were expanded to population doubling level (PDL) 9, representing chondrocytes ready for implantation. Cells at PDL3 were also used to serve as the minimally expanded control. Results showed that the treatment of FOXO4-DRI removed more than half of the cells in PDL9 but did not significantly affect the cell number of PDL3 chondrocytes. Compared to the untreated control, the senescence level in FOXO4-DRI treated PDL9 chondrocytes was significantly reduced. Based on the result from standard pellet culture, FOXO4-DRI pre-treatment did not enhance the chondrogenic potential of PDL9 chondrocytes. However, the cartilage tissue generated from FOXO4-DRI pretreated PDL9 cells displayed lower expression of senescence-relevant secretory factors than that from the untreated control group. Taken together, FOXO4-DRI is able to remove the senescent cells in PDL9 chondrocytes, but its utility in promoting cartilage formation from the in vitro expanded chondrocytes needs further investigation.